2019
DOI: 10.1080/14756366.2018.1555157
|View full text |Cite
|
Sign up to set email alerts
|

Do CO2and oxidative stress induce cancer?: a brief study about the evaluation of PON 1, CAT, CA and XO enzyme levels on head and neck cancer patients

Abstract: Head and neck cancer (HNC) is one of the most common malignancies in the world. HNC is a group of cancers that starts in the mouth, nose, throat, larynx, sinuses, or salivary glands. According to this section of the body parts; induction of cancer can be associated with CO2 and oxidative stress. The aim of this study is to assess the activities of carbonic anhydrase (CA), catalase (CAT), paraoxonase1 (PON1), and xanthine oxidase (XO) activities in 89 HNC patients and 115 healthy volunteers. Paraoxonase1 activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In addition, PON1 has esterase activity and degrades organophosphate xenobiotics such as paraoxon (C 10 H 14 N 1 O 6 P 1 ), phenyl acetate (C 8 H 8 O 2 ) and nerve agents [6]. Several studies have reported a decrease in serum PON1 activity in LC or HNC patients [3,9], and people exposed to organophosphate insecticides have a higher incidence of LC than the non-exposed population [10]. However, PON1 is not the only component of the HDL particles to have been associated with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PON1 has esterase activity and degrades organophosphate xenobiotics such as paraoxon (C 10 H 14 N 1 O 6 P 1 ), phenyl acetate (C 8 H 8 O 2 ) and nerve agents [6]. Several studies have reported a decrease in serum PON1 activity in LC or HNC patients [3,9], and people exposed to organophosphate insecticides have a higher incidence of LC than the non-exposed population [10]. However, PON1 is not the only component of the HDL particles to have been associated with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been reported that PON-1 plays an important role in atherosclerosis by protecting lipoproteins from oxidative modification [ 40 ]. It has been shown that a decrease in PON-1 activity may cause inflammation, which is considered a risk factor in the pathophysiology of many different diseases, and also oxidative stress [ 41 ]. Studies on PON-1 have been conducted in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is attached with the pathogenesis of gliomas since oxidative stress produces reactive oxygen species (ROS) which are resulting to stimulate the cancer progression 2 . The enzyme paraoxonase (PON1; EC 3.1.1.2) hydrolyses paraoxon to eliminate its harmful effects 3 . The calcium-dependent metalloenzyme PON1, which has an antioxidant effect, is responsible for the HDL particle-mediated reduction in lipid oxidation of low-density lipoproteins.…”
Section: Introductionmentioning
confidence: 99%